How to thrive in the next economy designing tomorrow's world today - Thackara, John (London, United Kingdom Thames & Hudson Ltd., 2015)
John Thackara has spent a lifetime roving the globe in search of design that serves human needs in a sustainable way. He believes that in our eagerness to find technological solutions to the big challenges faced by the human race, we have all too often ignored the astonishing creativity generated when people work together and in harmony with the world around them. Drawing on an inspiring range of examples, from a temple-led water management system in Bali that dates back hundreds of years to an innovative e-bike collective in Vienna, Thackara shows that below the radar of the mainstream media there are global communities creating a replacement economy from the ground up. Through a series of chapters each devoted to essential human concerns, he demonstrates that it is possible to live a rich and fulfilling life based on stewardship rather than exploitation of the natural environment. Ultimately optimistic, Thackara believes that through a huge variety of quiet, piecemeal changes of thought and action, we are coming to a tipping point: the end of one civilization but the beginning of another.
Changing : from do less harm, to leave things better -- Grounding : from heal the soil, to think like a forest -- Waterkeeping : from harvest the rain, to river recovery -- Dwelling : from depave the city, to pollinator pathways -- Feeding : from social farming, to food as a commons -- Clothing : from dirt to shirt, and soil to skin -- Moving : from two wheeled freight, to cloud commuting -- Caring : from cure to care, from me to we -- Commoning : from social money, to the art of hosting -- Knowing : from ways of seeing, to ways of acting.
Includes bibliographical references and index.
Includes bibliographical references (pages 183-184) and index.
Keywords: Environmental economics; Sustainable development; Sustainable design; Environmental policy -- Economic aspects